Estudio de la deserción estudiantil en la Facultad Jurídica, Social y Administrativa de la Universidad Nacional de Loja, durante los periodos académicos; abril-septiembre 2021 y octubre 2021 - marzo 2022 - Morocho Romero, Santiago Fernando (2024)
The present research project called "Study of Student Desertion in the Legal, Social and Administrative Faculty of the Universidad Nacional de Loja, during the academic periods; April-September 2021 and October 2021 - March 2022", was aimed at studying student dropout in the Faculty of Law, Social and Administrative in its 8 careers (Public Administration, Law, Economics, Tourism, Social Work, Accounting and Auditing, Finance, Business Administration) of the Universidad Nacional de Loja in the academic periods April-September 2021 and October 2021 - March 2022. The relevance of this research was to know why the students abandoned their careers at the UNL since the problem still exists today, and also to investigate their economic, labor, personal, etc. status. Also, to know the percentage of dropouts in these periods mentioned. For the present work, a mixed approach was applied, with a field and documentary approach, which type is exploratory and descriptive, non-experimental. The sample comprises 188 students from 8 careers of the two academic periods previously mentioned. Data were provided by UTI about FJSA. The techniques used for this study were a survey, which was addressed to the students. Additionally, an interview was used, it was directed towards the directors of the careers belonging to the Juridical, Social, and Administrative Faculty of the UNL. These elements helped to determine the fulfillment of the first specific objective, in which the causes, motives, and reasons that provoked the abandonment of the students of the Juridical Faculty of the Universidad Nacional de Loja were identified. Where it was possible to locate that 12.93% of students have dropped out of their careers, and the reasons for their withdrawal have been labor, academic, family, social, and others. To fulfill the second specific objective, a proposal for an administrative and pedagogical management model was made to reduce the dropout problem of students belonging to the FJSA of the Universidad Nacional de Loja.